PENGENALAN LITERASI KEUANGAN BAGI UMKM HOMESTAY UNTUK MEMPERMUDAH TRANSAKSI DAN TERHINDAR DARI SCAMMER - Effendi, Maya Syafriana; Farida, Farida; Malau, Melinda; Trisnawati, Nana; Shafenti, Shafenti; Budilaksono, Sularso; Syafrida Nasution, Evi; Firdaus, Venus; Sangkasari Paranita, Ekayana (Jurnal Abdi Insani, 2024)
Universitas Persada Indonesia YAI (UPI YAI) and 14 driving colleges in Jakarta and encompassing regions on October 27-28, 2023, teamed up in local area administration exercises in Cikolelet The travel industry Town, Serang Rule, Banten. The motivation behind this movement is to help neighborhood monetary turn of events and work on the personal satisfaction of nearby networks. Cikolelet The travel industry Town, situated in the Cinangka region, Serang Rule, turned into the focal point of consideration in the travel industry advancement endeavors and neighborhood business improvement. This people group administration included 56 instructors and 26 local area individuals who were tutored by members from 14 colleges. PKM members are separated into a few specialization calling gatherings. Where our PKM bunch gives Monetary Administration Preparing in Cikolelet Homestay MSMEs. The strategy for executing this action is show and joint conversation between the gathering and inhabitants who own and oversee homestays. From the consequences of the joint conversation, it tends to be inferred that the proprietor started to figure out straightforward monetary computations. Keywords: Homestay UMKM, Financial Literacy, Development Potential, Scammers